Desempenho motor, alcance e habilidades exploratórias em lactentes com risco biológico e risco ambiental - Rohr, Liz Araújo (2021)
Objectives: To verify the influence of biological and environmental risk factors in gross motor performance, reaching skills and exploratory abilities in infants at 6 months of age. Methods: This is a blind cross-sectional study. Methodological procedures are described for each outcome. (1) Motor performance (MP): 80 infants at six months of age (193.85 ± 9.08 days) of both sexes (39 boys and 41 girls) were included. MP was assessed using Alberta Infant Motor Scale. Biological and environmental characteristics were obtained using a questionnaire directed to parents. The following biological factors were investigated: gestational age, birth weight, birth length, while socioeconomic status (SES) was considered the environmental factor. (2) Reaching: Participated in this study 62 infants at six months of age divided into three independent groups: Group 1 (G1), 28 full-terms with no risk factors; Group 2 (G2), 19 full-terms classified as low SES and no biological risk; Group 3 (G3), 15 very preterm infants at six months corrected age and without low SES. Reaching was measured through kinematic analysis using the Qualisys® system, and the following variables were analyzed: straightness index, deceleration time, movement unit, reaching duration, mean and peak velocity. Furthermore, we analyzed proximal and distal reaching adjustments. (3) Exploratory behavior: Participated in this study 64 infants at six months of age, divided in three independent groups (G1, n=28; G2, n= 21; G3, n=15), as it was described for the reaching outcome (G1, n=28; G2, n= 21; G3, n=15). The exploratory behavior was coded as: fingering, mouthing, waving, tapping, banging, transferring, rotating, alternating, and squeezing. These actions were assessed with two types of toys: a malleable and a rigid. Results: (1) Chi-square test showed a significant association between socioeconomic status and motor performance (p = 0.0013), whereby infants with low socioeconomic status performed worse. However, multiple regression analysis showed associations between motor performance socioeconomic status (β=0.256; p=0.024) and birth weight (β=0.184; p=0.010). (2) Infants from G2 presented reaching duration (p = 0.032, Cohen’s f = 0.349) and movement unit (p = 0.033, Cohen’s f = 0.351) significantly higher than G3. Horizontal hand orientation was moderately associated with infants at environmental risk (p=0.031; Cramer’s V=0.30). (3) There was a significant difference between G2 vs G3 for fingering (p = 0.005), between G1 vs G3 for waving (p = 0.041) and between G1 vs G2 (p = 0.003) and G2 vs G3 (p=0,046) for transferring, to the malleable object. To the rigid object, there was a difference between G1 vs G3 for waving (p = 0.018) and between G2 vs G3 for transferring (p = 0.019). In addition, infants from G2 performed a lower total of abilities when compared to infants from G1, both for the malleable (p = 0.014) and the rigid toy (p = 0.007). Conclusion: Our results suggest that low SES has a greater influence on motor performance of infants at six months. Additionally, infants of low socioeconomic status perform less functional reaching movements than very preterm infants at six months corrected age. Regarding to exploratory behavior, each risk factor may influence manual exploration in a different way and infants with low socioeconomic seem to be at greater disadvantage than preterm infants. Based on these results, we highlighted that low-cost public health strategies are needed, providing to infants who have some risk factor, better opportunities of development.